Enhancement of Brillouin gain efficiency in multiwavelength L-band befl by utilizing bi-directional Brillouin pump amplification - Al-Mansoori M.H.; Mahdi M.A.; Jamaludin M.Z.; Din N.M.; Abdullah F. (Optical Society of American (OSA), 2023)
Enhancement of Brillouin gain efficiency in a multiwavelength L-band Brillouin-erbium comb fiber laser is presented. In this laser architecture, bi-directional amplification of the injected Brillouin pump signal within the erbium gain medium, before entering the single-mode fiber was utilized. Owing to this bi-directional preamplification of the Brillouin pump power, the requirement of a long single-mode fiber to increase the Brillouin gain efficiency was overcome. The shot length of a single-mode fiber was utilized to achieve a high number of output channels with high peak power. Up to 25 output channels with a constant wavelength separation of 0.089 nm were achieved at 170 mW of 1480 nm pump power and 0.54 mW of Brillouin pump power in a 0.5 km short single-mode fiber. 2010 Optical Society of America.